CONSIDERATIONS REGARDING HISTORY OF INTERIM FINANCIAL REPORTING - GRIGORAS-ICHIM, Claudia (Ecoforum Journal, 2016)
Financial reporting is nowadays, the basis of the decision making, investment and commercial and financial transactions. The present form of the financial reporting is based on history and human evolution, being observed even in Egyptian period. The paper is presenting the evolution of financial reports, underlining its stages, finalising with the appearance of interim financial statements. It is well recognised the internationalisation of the accounting statements and reports, as a result of the business and trade globalisation, the national borders being eliminated by common standards and principles.